Reader Response: Long-term Effect of Regular Physical Activity and Exercise Habits in Patients With Early Parkinson Disease. (30th August 2022) - Grippe, Talyta Cortez; Marras, Connie; Rafferty, Miriam; Lang, Anthony E.
Abstract : PPMI database analysis by Dr. Tsukita et al. reports the effects of physical activity on the progression of Parkinson disease (PD) clinical parameters, measured using the Physical Activity Scale for the Elderly (PASE). It confirms previous studies showing that regular exercise is associated with improved outcomes. 2 Although the study uses rigorous statistical methods, the reported association between maintained physical activity and concurrent slower deterioration of postural and gait stability should be interpreted carefully.